Antitumor activity of chLpMab‐2, a human–mouse chimeric cancer‐specific antihuman podoplanin antibody, via antibody‐dependent cellular cytotoxicity. (23rd March 2017) - Kaneko, Mika K.; Yamada, Shinji; Nakamura, Takuro; Abe, Shinji; Nishioka, Yasuhiko; Kunita, Akiko; Fukayama, Masashi; Fujii, Yuki; Ogasawara, Satoshi; Kato, Yukinari
Abstract: Human podoplanin (hPDPN), a platelet aggregation‐inducing transmembrane glycoprotein, is expressed in different types of tumors, and it binds to C‐type lectin‐like receptor 2 (CLEC‐2). The overexpression of hPDPN is involved in invasion and metastasis. Anti‐hPDPN monoclonal antibodies (mAbs) such as NZ‐1 have shown antitumor and antimetastatic activities by binding to the platelet aggregation‐stimulating (PLAG) domain of hPDPN. Recently, we developed a novel mouse anti‐hPDPN mAb, LpMab‐2, using the cancer‐specific mAb (CasMab) technology. In this study we developed chLpMab‐2, a human–mouse chimeric anti‐hPDPN antibody, derived from LpMab‐2. chLpMab‐2 was produced using fucosyltransferase 8‐knockout (KO) Chinese hamster ovary (CHO)‐S cell lines. By flow cytometry, chLpMab‐2 reacted with hPDPN‐expressing cancer cell lines including glioblastomas, mesotheliomas, and lung cancers. However, it showed low reaction with normal cell lines such as lymphatic endothelial and renal epithelial cells. Moreover, chLpMab‐2 exhibited high antibody‐dependent cellular cytotoxicity (ADCC) against PDPN‐expressing cells, despite its low complement‐dependent cytotoxicity. Furthermore, treatment with chLpMab‐2 abolished tumor growth in xenograft models of CHO/hPDPN, indicating that chLpMab‐2 suppressed tumor development via ADCC. In conclusion, chLpMab‐2 could be useful as a novel antibody‐based therapy against hPDPN‐expressing tumors. Abstract : Human podoplanin, a platelet aggregation‐inducing transmembrane glycoprotein, is expressed in different types of tumors. In this study, we developed chLpMab‐2, a human–mouse chimeric anti‐hPDPN cancer‐specific antibody. chLpMab‐2 could be useful as a novel antibody‐based therapy against hPDPN‐expressing tumors with no unexpected side effects.